Wheat Variety Response to Seeding Rate Across a Range of Kansas Environments in 2019–2020 - R. P. Lollato; B. R. Jaenisch (Kansas Agricultural Experiment Station Research Reports, 2021)
Due to the inconsistencies of wheat response to seeding rate, we conducted an experiment in seven Kansas locations during the 2019–2020 winter wheat growing season with the objectives of determining whether higher yielding environments warrant lower seeding rates than lower yielding environments, and whether this response depends on wheat variety. The wheat varieties ‘Larry,’ ‘SY Monument,’ ‘Tatanka,’ and ‘WB4303’ were seeded at 200,000, 400,000, 800,000, and 1,600,000 seeds per acre at Ashland Bottoms, Belleville, Conway Springs, Great Bend, Hutchinson, Leoti, and Manhattan. Growing season rainfall in the studied locations ranged from 6.7 to 24.2 inches, which corresponded to anywhere from 16 to 80% of the reference evapotranspiration. Stand count increased with increases in seeding rate but final population was dependent on the location: in Great Bend, the range in population evaluated was only from 248,270 to 464,590 due to an extremely dry period following wheat sowing; while at the other locations there was a larger range in populations evaluated. Regarding grain yield, plant population also interacted with location: grain yield increased linearly with increases in seeding rate in the five lowest yielding environments, and plateaued at 800,000 seeds/a in the two highest yielding environments. Likewise, varieties interacted with the location so that in two locations there were no varietal effects; while in five locations the difference between the lowest and highest yielding varieties ranged from 5.2 to 9.9 bushels per acre. These results suggested that wheat grain yield responses to seeding rate were dependent on location, and that varieties yielded differently by location but the response of the different varieties to seeding rate was similar.
Keywords: wheat; seeding rate; population; yield potential; variety